CURRENT APPROACHES TO REDUCING ALCOHOLISM IN THE REGION'S POPULATION (USING THE EXAMPLE OF THE KRASNOYARSK TERRITORY) - Андрей Владимирович Шульмин; Наталья Владимировна Тихонова; Ольга Юрьевна Кутумова (Медицина в Кузбассе, 2024)
Purpose of the study – update approaches to preventing the spread of alcohol and reducing the alcoholization of the population based on residents’ assessment of the legislative measures taken in the country aimed at reducing alcohol consumption.